Neuroprotective Effect for Cerebral Ischemia by Natural Products: A Review - Xie, Qian; Li, Hongyan; Lu, Danni; Yuan, Jianmei; Ma, Rong; Li, Jinxiu; Ren, Mihong; Li, Yong; Chen, Hai; Wang, Jian; Gong, Daoyin (Frontiers in Pharmacology, 2021)
Natural products have a significant role in the prevention of disease and boosting of health in humans and animals. Stroke is a disease with high prevalence and incidence, the pathogenesis is a complex cascade reaction. In recent years, it’s reported that a vast number of natural products have demonstrated beneficial effects on stroke worldwide. Natural products have been discovered to modulate activities with multiple targets and signaling pathways to exert neuroprotection via direct or indirect effects on enzymes, such as kinases, regulatory receptors, and proteins. This review provides a comprehensive summary of the established pharmacological effects and multiple target mechanisms of natural products for cerebral ischemic injury in vitro and in vivo preclinical models, and their potential neuro-therapeutic applications. In addition, the biological activity of natural products is closely related to their structure, and the structure-activity relationship of most natural products in neuroprotection is lacking, which should be further explored in future. Overall, we stress on natural products for their role in neuroprotection, and this wide band of pharmacological or biological activities has made them suitable candidates for the treatment of stroke.